Long response duration to pembrolizumab in metastatic, castration-resistant prostate cancer with microsatellite instability-high and neuroendocrine differentiation: A case report - Yoshida, Tsukasa; Yaegashi, Hiroshi; Toriumi, Ren; Kadomoto, Suguru; Iwamoto, Hiroaki; Izumi, Kouji; Kadono, Yoshifumi; Ikeda, Hiroko; Mizokami, Atsushi (Frontiers in Oncology, 2022)
Background The detection of microsatellite instability in urologic cancers is rare, especially in metastatic, castration-resistant prostate cancer with neuroendocrine differentiation. Case presentation This is a case of a 66-year-old Asian male patient with prostate adenocarcinoma who had metastases at initial presentation. Despite combined androgen deprivation therapy, his prostate-specific antigen (PSA) progressively increased, and prostate re-biopsy revealed small cell carcinoma. He was treated with platinum-based systemic chemotherapy, and his tumor markers, including PSA, remained negative; however, his local symptoms worsened. Subsequently, microsatellite instability-high was detected, and pembrolizumab was administered resulting in complete remission with the resolution of symptoms and continued therapeutic effect for more than 14 months. Conclusion Microsatellite instability testing should be considered, despite its low detection rate, because the response to pembrolizumab in metastatic, castration-resistant prostate cancer with detectable microsatellite instability is associated with a prolonged duration of response.